Application of Emphatic Marketing Strategy at Burger King Company on Social Media Against Customer Engagement During the Covid-19 Pandemic - Risky Al Hamdhan (Universitas Tidar, 2021)
The COVID-19 pandemic that has been going on since the beginning of 2020 hashad a tremendous impact on all business sectors. Several sectors experienced a decline, not even a few went bankrupt. One of the companies that managed to survive in the midst of a pandemic is Burger King. By utilizing social media accounts, Burger King is able to optimally implement empathic marketing strategies so as to increase customer engagement. This study uses a qualitative descriptive method with a phenomenological approach. This research method will focus on studying and explaining the phenomenon of the marketing strategy used by Burger King duringthe COVID-19 pandemic. The object of this research is on Burger King's social media pages, namely Instagram (@burgerking.id) and Facebook (Burger King Indonesia). The image post containing the marketing strategy was uploaded on November 3, 2020 or when the COVID-19 pandemic was taking place in Indonesia. One of the latest marketing strategies is to create exclamation content as well as invitations to be uploaded on their official social media which contains an invitation to Burger King to its customers to buy products from various other restaurants, including its competitors, namely McDonald's and KFC. Burger King also recommends its customers to buy from several other fast food/restaurants such as Pizza Hut, Wendy's, Hokben, J.Co, RM Padang Simple, to Warteg. This marketing strategy generates a lot of empathy and respect from netizens to help and invite each other in terms of buying products from the fast food.